Search for Expectancy-Inconsistent Information Reduces Uncertainty Better: The Role of Cognitive Capacity - Strojny, Paweł; Kossowska, Małgorzata; Strojny, Agnieszka (Frontiers in Psychology, 2016)
Motivation and cognitive capacity are key factors in people’s everyday struggle with uncertainty. However, the exact nature of their interplay in various contexts still needs to be revealed. The presented paper reports on two experimental studies which aimed to examine the joint consequences of motivational and cognitive factors on incomplete information preference. In Study 1 we demonstrate the interactional effect of motivation and cognitive capacity on preference for expectancy inconsistent information with a high need for closure resulting in a stronger relative preference for expectancy-inconsistent information among non-depleted individuals, but the opposite among cognitively depleted ones. This effect was explained by the different informative value of questions in comparison to affirmative sentences and the potential possibility of assimilation of new information if it contradicts prior knowledge. In Study 2 we further investigated the obtained effect, showing that not only questions but also other kinds of incomplete information are subject to the same dependency. We discuss the obtained effect in the context of previous assumptions that high need for closure results in a simple processing style, advocating a more complex approach based on the character of the provided information.